The influence of product innovation, halal labeling, and digital marketing on the decision to purchase processed milkfish - Tri Arini Diana Haqiqi, Niswatun Hasanah (LPPM Institut Agama Islam Qomaruddin Gresik, 2025)
ABSTRAC Purchasing decisions are actions taken by customers to achieve goals as quickly as possible and overcome problems that occur. This research aims to determine whether product innovation, halal labels and digital marketing variables partially influence purchasing decisions. Sampling used the Non Probability Sampling method with the Cochrant technique. The data analysis used is quantitative analysis which includes: research instrument testing, classical assumption testing, multiple linear regression testing, hypothesis testing. The research results show that the product innovation variable obtained a value of tcount (5.188) > ttable (1.661) and a sig value of 0.000. The halal label variable obtained a value of tcount (4.392) > ttable (1.661) and a sig value of 0.000. The digital marketing variable obtained a value of tcount (1.769) > ttable (1.661) and a sig value of 0.080. It can be interpreted that the product innovation and halal label variables have a positive and significant effect on purchasing decisions, while the digital marketing variables do not have a significant effect on purchasing decisions. The results of the F test obtained a value of Fcount (77.728) > Ftable (2.704), which means that all variables have an influence on purchasing decisions. The coefficient of determination (R2) is (0.708), which means that product innovation, halal labels, digital marketing influence consumer purchasing decisions for Omah Assyifa's milkfish food by 70.8% while the remaining 29.2% is influenced by other variables not discussed in this research. . Keywords: Product Innovation, Halal Label, Digital Marketing, Purchasing Decisions. ABSTRAK Keputusan pembelian merupakan tindakan yang dilakukan customer untuk memperoleh tujuan dengan secepat mungkin dan mengatasi permasalahan-permasalahan yang terjadi. Penelitian ini bertujuan untuk mengetahui variabel inovasi produk, label halal, dan digital marketing secara parsial berpengaruh terhadap keputusan pembelian. Pengambilan sampel menggunakan metode Non Probability Sampling dengan teknik Cochrant. Analisis data yang digunakan berupa analisis kuantitatif yang meliputi: uji instrumen penelitian, uji asumsi klasik, uji regresi linier berganda, uji hipotesis. Hasil penelitian menunjukkan bahwa variabel inovasi produk memperoleh nilai thitung (5,188) > ttabel (1,661) dan nilai sig 0,000. Variabel label halal memperoleh nilai thitung (4,392) > ttabel (1,661) dan nilai sig 0,000. Variabel digital marketing memperoleh nilai thitung (1,769) > ttabel (1,661) dan nilai sig 0,080. Dapat diartikan bahwa variabel inovasi produk dan label halal berpengaruh positif dan signifikan terhadap keputusan pembelian sedangkan variabel digital marketing tidak berpengaruh signifikan terhadap keputusan pembelian. Hasil uji F memperoleh nilai Fhitung (77,728) > Ftabel (2,704) yang berarti semua variabel berpengaruh terhadap keputusan pembelian. Nilai koefisien determinasi (R2) sebesar (0,708) yang berarti inovasi produk, label halal, digital marketing mempengaruhi keputusan pembelian customer olahan bandeng omah Assyifa sebesar 70,8% sedangkan sisanya 29,2% di pengaruhi oleh variabel lain yang tidak dibahas dalam penelitian ini. Kata Kunci: Inovasi Produk, Label Halal, Digital Marketing, Keputusan Pembelian.